2020
DOI: 10.21037/jtd.2020.01.69
|View full text |Cite
|
Sign up to set email alerts
|

Mitral regurgitation after transcatheter aortic valve replacement

Abstract: Patients undergoing transcatheter aortic valve replacement (TAVR) might have an associated significant MR that can potentially lead to left ventricular (LV) failure after procedure. Considering the specific alterations in the mitral valve in TAVR scenario and the widespread use of TAVR in recent years, it appears important to know and understand the anatomical, functional and clinical implications to develop adequate strategies for the future. Patients with severe mitral regurgitation (MR) have been generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
(157 reference statements)
0
6
0
Order By: Relevance
“…Being in close contact with the left fibrous trigone (2,17), the AML is prone to interference with the prosthetic valve. In fact, our previous study found that in patients with pure native aortic valve regurgitation, 14 of 61 (23.0%) patients who received Venus-A prosthesis implantation had significant PAI following TAVR (18).…”
Section: Discussionmentioning
confidence: 99%
“…Being in close contact with the left fibrous trigone (2,17), the AML is prone to interference with the prosthetic valve. In fact, our previous study found that in patients with pure native aortic valve regurgitation, 14 of 61 (23.0%) patients who received Venus-A prosthesis implantation had significant PAI following TAVR (18).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the MitraClip procedure is recommended in patients with disproportionate secondary mitral regurgitation in which severe MR is coupled with nonseverely dilated left ventricular chambers [95,96]. Although this new framework is a very attractive proposal, however, it does not find unanimous consensus and requires further deep investigation involving transcatheter heart valve therapy [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127].…”
Section: Discussionmentioning
confidence: 99%
“…TMViV-T is presently considered in the United States and Europe for the management of deteriorated MV (TMViV) or mitral ring (TMViR) prostheses in patients at high risk for standard surgical approach [17,18] . Unlike Mitraclip therapy, in which the legislative endorsement is based on the results reported from the Endovascular Valve Edge-to-Edge Repair randomized Study (EVEREST) [19] , there is poor evidence on the survival benefit in patients who have undergone TMViV/TMViR for deteriorated bioprostheses compared to those who had redo surgery for SVD of MV [3,14,15,17,19] .…”
Section: The Emerging New Contribution Of Transcatheter Mitral Valve-in-valve Therapymentioning
confidence: 99%
“…Both procedures had the same enrollment method for the patients who were considered suitable for the use of devices, therefore 349 persons from 98 sites were included in the US registry from 2013 to 2015 [26] . Nevertheless, the recent literature shows that the transcatheter procedure with the use of Mitraclip has a slight advantage over TMViV-T due to a better understanding of the pathophysiology of mitral rigurgitation and the normalization of the geometry [2][3][4]8,9,[27][28][29][30] .…”
Section: The Emerging New Contribution Of Transcatheter Mitral Valve-in-valve Therapymentioning
confidence: 99%
See 1 more Smart Citation